Analysis of Motorized Vehicle Taxpayer Compliance Before and During the Covid-19 Pandemic (Case Study of the East Java Provincial Government UPT Regional Revenue Agency. Sumenep Regional Revenue Management) - Fatima Azarha; Isnani Yuli Andini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This researcher aims to analyze the compliance of motor vehicle tax payers before and during the covid-19 pandemic. In this study uses qualitative methods by analyzing data obtained from observations, interviews with key informants and supporting informants related to motor vehicle tax compliance. The data analysis technique used in this research is by using data reduction, data presentation and drawing conclusions. The results of this study indicate that motor vehicle taxpayer compliance is influenced by factors, namely tax knowledge, taxpayer awareness, economy, location, social distancing